Phytochemical screening and in vitro antioxidant activity of ananas comosus (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
The objective of this study was to determine the phytochemical screening and antioxidant activity of ananas comosus L. Different concentration of ethanol and aqueous were used to extract the phenolic compounds. The antioxidant activity of the pineapples was measured using the DPPH radical scavenging assay, hydrogen peroxide scavenging activity, total antioxidant activity. 10% ethanol was chosen as the best solvent for analyzing the antioxidant activity of pineapples. The pineapple was found to contain the highest antioxidant activity. This was also found to have the highest DPPH scavenging activity, total antioxidant and hydrogen peroxide scavenging activity. This different were observed between the ascorbic acid content. The result shows that pineapple and its active constituents may be used in further antioxidant therapy.